Lucretia Borgia : according to original documents and correspondence of her day - Gregorovius, Ferdinand, 1821-1891; Garner, John Leslie; Garner, John Leslie (New York : D. Appleton and company, 1903)
"Lucrezia Borgia (Italian pronunciation: [lukrtsja brd{7f0292}a]; Catalan: Lucrècia; Catalan pronunciation: [lukrsi]; 18 April 1480 ? 24 June 1519) was the daughter of Pope Alexander VI, and Vannozza dei Cattanei. Her brothers included Cesare Borgia, Giovanni Borgia, and Gioffre Borgia. Lucrezia's family later came to epitomize the ruthless Machiavellian politics and sexual corruption alleged to be characteristic of the Renaissance Papacy. Lucrezia was cast as a femme fatale, a role she has been portrayed as in many artworks, novels, and films. Very little is known of Lucrezia, and the extent of her complicity in the political machinations of her father and brothers is unclear. They certainly arranged several marriages for her to important or powerful men in order to advance their own political ambitions. Lucrezia was married to Giovanni Sforza (Lord of Pesaro), Alfonso of Aragon (Duke of Bisceglie), and Alfonso I d'Este (Duke of Ferrara)."--Wikipedia.
Mode of access: Internet.
Keywords: Borgia, Lucrezia, -- 1480-1519; 1492-1559; Renaissance -- Italy; Italy -- History -- 1492-1559; History